3′-R/S-Hydroxyvoacamine, a potent acetylcholinesterase inhibitor from Tabernaemontana divaricata - Chaiyana W. (2014)
Guided by the acetylcholinesterase inhibiting activity, the bisindole alkaloid 3′-R/S-hydroxyvoacamine was isolated from a stem extract of Tabernaemontana divaricata, a plant used in Thailand in traditional rejuvenation remedies for improving the memory. The structure of the alkaloid was elucidated by extensive use of NMR spectroscopy and the complete assignment of the 1H and 13C NMR spectra is reported. The alkaloid acted as a non-competitive inhibitor against AChE with an IC50 value of 7.00 ± 1.99 μM. An HPLC method was developed for the quantitative analysis of the AChE inhibitor. It suggested that there was 12.4% (w/w) of 3′-R/S-hydroxyvoacamine in the alkaloid enriched fraction of T. divaricata stem. © 2013 Elsevier GmbH. All rights reserved.